Peran Esktrakurikuler Pencak Silat Sapu Jagat Cimande dalam Pembinaan Sikap Religius Peserta Didik di SDN Rawa Endah Bogor - Hadid Athoriq; Achmad Junaidi Sitika; Nurhasan Nurhasan (LP. Ma'arif Janggan Magetan, 2024)
This research aims to find out the reality of the activities carried out by the extracurricular Pencak Silat Sapu Jagat Cimande in fostering students’ religious attitudes at SDN Rawaendah Bogor, the supporting factors and obstacles to fostering religious attitudes in students at school, and the results achieved regarding the development of participants’ religious attitudes. Students from Pencak Silat extracurricular activities by the Sapu Jagat Cimande Pencak Silat school at SDN Rawaendah Bogor. The approach used in this research is a qualitative research approach and method, the method and approach includes an in-depth perception of the phenomenon or problem being studied by studying the phenomenon in more detail in cases where the nature of the problem being studied can be different. Therefore, research using qualitative methods can be said to be good, if the data collected must be accurate, complete in the form of primary and secondary data. The results of this research show that the Pencak Silat Sapu Jagat Cimande extracurricular activities on the development of students’ religious attitudes at SDN Rawaendah Bogor are that students who are involved in the Sapu Jagat Cimande Pencak Silat extracurricular activities show positive development academically and behaviorally. Apart from that, the school also saw positive changes in students’ religious attitudes and moral development which was initially not good. This shows that these extracurricular activities not only provide physical and mental benefits, but also support the formation of better character for our students and foster students’ religious attitudes in a better direction as well.